From 'Capture to Courtroom': Collaboration and the Digital Documentation of International Crimes in Ukraine. (8th November 2022) - Koenig, Alexa
Abstract: The past decade has witnessed a profound shift in the documentation of war crimes and other serious international crimes. Whereas evidence collection has traditionally been conducted by legally mandated investigators, and focused on interviewing witnesses as well as gathering and preserving physical and documentary evidence, conventional forms of fact-gathering are now being supplemented by abundant digital documentation gathered by a dispersed network of individuals and organizations that represent a broad array of disciplines. This shift has been facilitated by two important developments: first, a transition in modes of information sharing from analogue to digital sources, including from older generation technologies like the telephone and fax to online platforms like TikTok and Telegram. Secondly, an increased understanding that digital documentation requires both a collaborative and multidisciplinary approach to data collection, storage, processing, analysis and presentation. In this comment, I outline the many investigative stages in which cross-organizational and multi-disciplinary collaboration are taking place, both informally and formally; briefly discuss some of the weaknesses and strengths of such collaborations; and explore what these changes mean for international criminal justice more generally.